The right isotherms for the right reasons?: validation of generic force fields for prediction of methane adsorption in metal-organic frameworks - Lennox, Matthew J.; Bound, Michelle; Henley, Alice; Besley, Elena (Taylor & Francis, 2017)
In recent years, the use of computational tools to aid in the evaluation, understanding and design of advanced porous materials for gas storage and separation processes has become ever-more widespread. High-performance computing facilities have become more powerful and more accessible and molecular simulation of gas adsorption has become routine, often involving the use of a number of default and commonly-used parameters as a result. In this work, we consider the application of molecular simulation in one particular field of adsorption – the prediction of methane adsorption in metal-organic frameworks in the low-loading regime – and employ a range of computational techniques to evaluate the appropriateness of many commonly chosen simulation parameters to these systems. In addition to confirming the power of relatively simple generic force fields to quickly and accurately predict methane adsorption isotherms in a range of MOFs, we demonstrate that these force fields are capable of providing detailed molecular-level information which is in very good agreement with quantum chemical predictions. We highlight a number of chemical systems in which molecular-level insight from generic force fields should be approached with a degree of caution and provide some general recommendations for best-practice in simulations of CH4 adsorption in MOFs.